Leaching behavior of fly ash from co-firing of coal with alternative off gas fuel in powerplant boilers. (June 2018) - Stefaniak, Sebastian; Kmiecik, Ewa; Miszczak, Ewa; Szczepańska-Plewa, Jadwiga; Twardowska, Irena
Abstract: The attenuation of climate changes through substitution of coal with GHG-neutral or low-emission fuels, a replacement of non-renewable resources with renewable ones and reuse of waste materials is being achieved among others by partial or total substitution of coal in power plants with alternative fuels that may affect the composition and leaching behavior of coal fly ash (CFA), and therefore its environmental impact in disposal/reuse sites. A comparison of the most widespread primary alkaline Class F CFA of Sialic type from coal combustion with fly ash from co-combustion of the same coal with process off gas in powerplant boilers (CGFA – coal/gas fly ash) revealed certain reduction of pH, CaO, MgO and Fe2 O3, and simultaneous increase of other major and minor constituents, but in particular of almost all trace element contents (by 35% - 2-fold). However, comparative tests of the leaching behavior of both materials as a function of L/S (Liquid/Solid ratio) and extract pH with the use of recently developed US EPA, SW-846 Methods 1316 and 1313 (2012) showed that the mobility of both major and trace elements in both residuals (apart from their properties as cations, oxyanions and amphoteric species) was governed by several factors, among them availability and equilibria constraints, and followed predominantly a similar pattern. Liquid-solid partitioning as a function of L/S showed higher release of Ca, OH, As, Ba, Br, I, Co, Ni, Sb, Pb and W from CFA, and of Al, Na, K, SO4, Si, B, Cd, Cr, Hg, Li, Mo, Ti and V from CGFA, Se and Sr showed similar leachability, while Ag, Be, Cu, Fe, Mg, Mn, Tl, Zn, Zr were equally immobile. The decisive factor in element release from CFA and CGFA as a function of pH was the pattern of acid/base neutralization capacity (ANC/BNC) of both materials that in CFA and CGFA appeared to be basically different. Due to the gradual reduction of ANC in CGFA opposite to its sharp depletion in CFA, the majority of elements unstable at acidic pH (Ag, Al, As, Ba, Be, Cd, Cu, Fe, Mn, Ni, Pb, Sb, Si, Ti, Tl, V, W, Zn, Zr) were less susceptible to mobilization from CGFA than from CFA. Along with the lower mobility of a number of elements in the entire (Ca, Mg, Cl, Br, Cr), or neutral/acidic (Fe, Mn, Ni, Sb, PO4 ), or alkaline range (I, Se, CO3 ), and similar release of K, SO4, Co and Hg, at less developed active surface and interconnected micro-porosity, this makes CGFA from process off gas co-combustion environmentally safer than CFA. Highlights: The first study of leaching behavior of fly ash from coal/gas co-combustion (CGFA). The first time use of new US EPA leaching methods to coal/gas co-combustion fly ash. CGFA contains higher concentrations of trace elements than coal fly ash (CFA). Patterns of acid neutralization capacity (ANC) of CFA and CGFA are different. CGFA from off gas co-combustion shows lesser release of trace elements than CFA.